2022
DOI: 10.1523/jneurosci.2098-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Induced Pronociceptive Signaling in the Gastrointestinal Tract Is Mediated by Delta-Opioid Receptor Signaling

Abstract: Opioid tolerance (OT) leads to dose escalation and serious side effects, including opioid-induced hyperalgesia (OIH). We sought to better understand the mechanisms underlying this event in the gastrointestinal tract. Chronicin vivoadministration of morphine by intraperitoneal injection in male C57BL/6 mice evoked tolerance and evidence of OIH in an assay of colonic afferent nerve mechanosensitivity; this was inhibited by the δ-opioid receptor (DOPr) antagonist naltrindole when intraperitoneally injected in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…5,15 Furthermore, our previous studies have shown that opioid responses in visceral DRG neurons did not differ between female and male mice. 19,50 Such findings are consistent with the current evidence on sex differences in opioid analgesia, suggesting sex-specific therapeutic interventions are not warranted. 11,12 The cumulative actions of opioids and their metabolites with repeated dosing could amplify potential on-target side effects or could cause tolerance.…”
Section: Discussionsupporting
confidence: 84%
“…5,15 Furthermore, our previous studies have shown that opioid responses in visceral DRG neurons did not differ between female and male mice. 19,50 Such findings are consistent with the current evidence on sex differences in opioid analgesia, suggesting sex-specific therapeutic interventions are not warranted. 11,12 The cumulative actions of opioids and their metabolites with repeated dosing could amplify potential on-target side effects or could cause tolerance.…”
Section: Discussionsupporting
confidence: 84%
“…Of note, two biochemical studies have raised doubts about the specificity of Pitstop-2 as a clathrin inhibitor ( Dutta et al, 2012 ; Willox et al, 2014 ). However, there are also numerous studies showing Pitstop-2 to specifically block clathrin-dependent processes in neurons ( von Kleist et al, 2011 ; Merriam et al, 2013 ; Neef et al, 2014 ; Missig et al, 2017 ; DiCello et al, 2019 ; Gomez et al, 2021 ; Zhang et al, 2021 ; Jaramillo-Polanco et al, 2022 ). Nevertheless, potential off target effects of Pitstop-2 need to be considered with respect to our results.…”
Section: Limitations and Conclusionmentioning
confidence: 99%